Distribution of thallium in soil and plants growing in the Keban Mining district of Turkey and determined by ICP-MS - Şaşmaz, Ahmet; Şen, Özlem; Kaya, Gökçe; Yaman, Mehmet; Sağıroğlu, Ahmet (My University, 2007)
In this study, we examined the Tl concentrations in soil and plants taken from an abandoned Pb-Zn-Cu mining area (Keban, Turkey). This region contains Pb, Zn, and Ag sulphide mineralizations that have been mined for 6000 years. For this purpose, soil and plant parts (including roots and shoots) were taken from 20 points in that area and the Tl concentrations determined by ICP-MS. The plants Euphorbia macroclada, Verbascum cheiranthifolium Boiss, and Astragalus gummifer were examined. The Tl levels in the soils ranged from 3.0–27.6 mg kg–1 which is 3–27 times higher than in uncontaminated soils (1.0 mg kg–1). The observed Tl levels in plant parts ranged from 0.05–4.62 mg kg–1 which is up to 92-times higher than the allowable levels (0.05 mg kg–1) proposed in the literature. It was also observed that high concentrations of metals such as Mo, Cu, Pb, Zn, Ag, and As inhibit the Tl uptake by plant roots and shoots.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Thalium; Keban; Terrestrial plants